JOB SHADOWING AS A METHOD IN FURTHER EDUCATION - Margeviča-Grinberga, Ieva; Kalēja, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In response to the advanced shifts within the professional era, this study underscores the novel application of job shadowing as a medium of further education. By providing an understanding of the shifting requirements for practical knowledge in career building, this research represents the various scenarios of job shadowing for advanced professional growth. This study employed a mixed-methods approach employed quantitative surveys and qualitative interviews. The responses of 63 professionals from various industries involved in job shadowing were thoroughly analysed. The responses demonstrate the significant impact of job shadowing on acquiring skills and developing career trajectories. The respondents emphasise the importance of acquiring extensive practical knowledge, obtaining precise and reliable information about various professional job positions, and increasing their confidence to the most extent. Further, job shadowing is also helpful in expanding professional networks. This approach also contributes to a broader scenario on career-building journeys. Other than these positive outcomes, challenges were also underlined. These include a limited number of opportunities and not enough knowledge of employees in this field. This study represents the shifting position of job shadowing and recommends practical suggestions for establishing its efficiency in the professional corporate world. This study provides a detailed overview of the benefits, challenges, and solutions aligned with job shadowing. The study also highlights the important role of new strategies in further education in the recent discussion.